A Clinical Guide to the Treatment of the Human Stress Response - Everly, George S. (Plenum Series on Stress and Coping, 2002)
Over a decade has passed since the first edition of this critically acclaimed volume was published. Much is new, but much has remained the same. The reader will find that the primary efferent biological mechanisms of the stress response are largely the same as described in 1989. This underscores the br- liance of Selye, Cannon, Mason, Gellhorn, and Levi as they sought to elu- date the anatomical and physiological constituents of human stress. New information has been generated regarding the microanatomy, biochemistry, and genetic aspects of the human stress response. Furthermore, the anatomy and physiology of posttraumatic stress has been more thoroughly elucidated. The important role of cognitive processes in the determination of sub- quent stress arousal remains underscored and has been empirically validated by subsequent research (Smith, Everly, & Johns, 1992, 1993). The ỚSredisc- eryỚ<U+00fd> of the importance of positive psychology and optimism is consistent with our earlier etiological emphasis upon the cognitiveỚ<U+001c>affective domain in the overall phenomenology of human stress.